Hepatoprotective Activity of Ethyl Acetate Fraction of Senggugu’s Root Bark (Clerodendrum serratum L.Moon) on Rats Induced by CCl4 - Nasrudin, Nasrudin; Wahyono, Wahyono; Mustofa, Mustofa; Asmah, Ratna (Indonesian Journal of Pharmacy, 2017)
Senggugu is a plant that has long been used to treat syphilis, typhoid, cancer, jaundice, and hypertension. The pharmacological activity of senggugu in Indonesia that have been reported include antifertility activity in leaves, mucolytic activity, anti-inflammatory and tracheospasmolytic, also antioxidant in its root bark. This study aims to determine the hepatoprotective effect of ethyl acetate extract fraction of senggugu’s root bark in rats induced by CCl4. The powder of senggugu’s root bark was extracted by terraced maceration method starts from n-hexane, ethyl acetate, to methanol, thus obtained ethyl acetate extract fraction of senggugu’s root bark (FEAKAS). The ethyl acetate extract fractions were then tested for hepatoproctective activity using doses of 25, 50, and 100 mg/Kg.BW on rats induced by CCl4. FEAKAS hepatoprotective activity was determined from the analysis of blood biochemical and oxidative stress parameters. The blood biochemical parameters included SGOT (serum glutamic oxaloacetic transaminase), SGPT (serum glutamic pyruvic transaminase), ALP (alkaline phosphatase), bilirubin, and total protein were measured with test kit. The oxidative stress parameters were measured from homogenates of liver tissue that were prepared by adding 500 mL of 50 nM Tris buffer (pH 7.4) containing 1 mM EDTA and 10 µg/mL leupeptin. The homogenates were centrifuged to obtain supernatants for measurement of oxidative stress parameters using spectrophotometer method, including MDA (malondialdehyde), GPx (glutathione peroxidase) and CAT (catalase). The results showed that the effect of FEAKAS against CCl4 induction for preventing lipid peroxidation, from both blood chemical and oxidative stress parameters, are shown at a dose of 100 mg/Kg.BW that significantly different compared to CCl4 control (ρ <0.05) on all blood chemical and oxidative stress parameters.